Creative self‐efficacy as mediator between creative mindsets and creative problem‐solving - Royston, Ryan; Reiter‐Palmon, Roni (The Journal of creative behavior)
An emerging area of research is how one's mindset regarding the fixedness and malleability of creative ability relates to creative performance. Malleable creative mindsets tend to be positively related to creativity while fixed mindsets often show a negative association. Similarly, creative self‐efficacy, or one's beliefs that they have the capacity to be creative, is also related to creative performance and creative mindsets. While previous studies tested the direct relationship between mindsets and creativity, this study tested creative self‐efficacy in this relationship. A total of 152 students from a Midwestern university participated in the study. They were provided with measures of creative self‐efficacy, creative mindsets, and creative problem‐solving. Solutions were assessed in terms of quality and originality. Results indicated that both malleable creative mindsets and creative self‐efficacy were positively related to solution quality and originality while fixed creative mindsets were negatively related. Mediation analysis using Preacher and Hayes' (2004) bootstrapping macro showed that creative self‐efficacy mediated the relationship between malleable mindsets and quality and originality as well as the relationship between fixed mindsets and quality and originality. This research advances the study of creativity by demonstrating that creative self‐efficacy is an important mechanism through which creative mindsets relate to creative performance.